Manajemen Biaya Produksi dan Strategi Penetapan Harga pada Industri Batik dalam Pengembangan Desa Kreatif - Alwie, Alvi Furwanti; Azlina, Nur; Taufik, Taufeni; Luthfi iznillah, Muhammad; Eka Maulana, Gilang; Riovi Ramadhan, Gian (Akuntansi & Ekonomika, 2024)
This study analyzes production cost management and pricing strategies in the batik industry at BUMDesa Langgam Sako, Desa Teluk Latak, Bengkalis Regency. Utilizing a descriptive qualitative approach, the research aims to identify key production cost components and develop pricing strategies that align with market characteristics. Data were collected through semi-structured interviews, Focus Group Discussions (FGDs), and secondary data analysis. The findings indicate that efficient cost management is crucial for setting competitive prices and supporting creative village development. The proposed model enables BUMDesa Langgam Sako to strengthen its market position, expand distribution reach, and contribute to sustainable village economic growth. This research provides practical guidance for entrepreneurs and policymakers in managing creative industries in rural areas.